Principles of Genetics - Snustad, D. Peter (John- Wiley, 2006)
An examination of the field of genetics, with an emphasis on applications. Written primarily for students, this book provides up-to-date coverage of the most recent techniques used in modern genetics, such as gene cloning and plot analyses of genes and gene products.